Detection of Mitochondrial Mutations Through Isothermal Nucleic Acid Amplification Coupled With Clustered Regularly Interspaced Short Palindromic Repeat-Associated Endonuclease Cas13a - Jiang, Hua; Duan, Kun; Han, Xu; Wang, Jun; Liu, Xiao; Yan, Maoxiao; Wang, Yunxiu; Liu, Hongyan; Shi, Huiling; Gao, Xiaoqing; Ouyang, Chuan; Fu, Xue; et al. (Frontiers in Genetics, 2021)
The clustered regularly interspaced short palindromic repeat (CRISPR)-associated endonuclease Cas13a can specifically bind and cleave RNA. After nucleic acid pre-amplification, bacterial Cas13a has been used to detect genetic mutations. In our study, using a transcription-mediated amplification together with Cas13a, we can isothermally amplify and detect mitochondrial point mutations under non-denaturing conditions from human genomic DNA. Unlike previous reports, we prepared CRISPR DNA with T7 promoter sequences and generated CRISPR RNA via transcription-mediated amplification instead of synthesizing and adding CRISPR RNA in a separate step. As a proof-of-concept, we showed that both m.1494C > T and m.1555A > G mutations were detected within 90 min. In addition, we explored various designs of CRISPR DNA to improve assay specificity, including the location and number of nucleotide mismatches, length of protospacer sequence, and different buffering conditions. We also confirmed the possibility of a “one-step single-tube” reaction for mutation detection. This assay can robustly distinguish circular DNA templates that differ by a single nucleotide. It has the potential to be adapted for automated applications, such as the screening of mitochondrial diseases.